A Strategy Framework to Boost Conversational AI Performance - Christian Hildebrand; Sophie Hundertmark (Marketing Review St.Gallen, 2021)
The development of conversational AI applications is often more tactical than strategic; more technology-focused than focused on the end user and the problem to be solved. This paper provides a strategy framework to structure the effective development of conversational AI in research and practice.
Keywords: 650